- Teamwork - Fadilla, Hasana; Hayati, Fitri (Indikator Pendidikan Indonesia, 2022)
Teamwork is the collaborative effort of a group to achieve a common goal or complete a task in the most effective and efficient way as a group. Working together allows colleagues to get to know each other better and build strong social relationships. Collaboration allows everyone to be valued for their abilities. This creates a more positive and relaxed work atmosphere. The research methodology used in this study was to conduct a literature study of 15 journal articles with a collaborative team which was published on several websites over the last 5 years. The research finding that 2-way communication is needed to build teamwork. That way, team members can freely express their opinions, want to listen to each other's opinions, and find solutions to problems together. In a good team, each member must know the responsibilities and tasks they carry out in a project. They must also have the integrity to carry out all their responsibilities properly. All difficulties and obstacles must be discussed and resolved together.